Biennale de l'Image en Mouvement (Biennial of Moving Image) '21: A Goodbye Letter, A Love Song, A Wake-Up Call, curated by DIS and Andrea Bellini. (1st April 2022) - Walsh, Maria
Biennale de l'Image en Mouvement (Biennial of Moving Image) '21: A Goodbye Letter, A Love Song, A Wake-Up Call, curated by DIS and Andrea BelliniCentre d'Art Contemporain Genève, Geneva, 12 November 2021‐20 February 2022